Analisis Perbandingan Distribusi Kecepatan Angin Untuk Mengetahui Probabilitas Kecepatan Angin di Pulau Jawa - I Made Putra Ananta W; Mardi Santoso; Mohammad Abu Jami'in; George Endri Kusuma; Didik Sukoco (Proceedings Conference on Marine Engineering and its Application, 2023)
- Wind speed is the movement of air from areas of high pressure to areas of lowpressure. As the use of electric energy increases due to the growing human population in aregion, there is a need for renewable energy sources to convert renewable energy intoelectricity. Wind energy is highly potential if utilized, considering its relatively low utilizationfor electricity generation in Indonesia. In the initial stage of using wind energy for electricitygeneration, data on the wind potential of a region is required, thus an analysis of wind speedin several areas on Java Island is necessary. The wind speed data in this Final Projectincludes several regions in the Java Province, namely: Bandung, Banyuwangi, Bekasi,Gresik, Kudus, Malang, Semarang, Surabaya, Surakarta, and Tuban. The method used inmodeling wind speed involves the Weibull distribution, Rayleigh distribution, and Gammadistribution. Goodness-of-fit tests are applied to examine the best probability functions ofeach distribution to be analyzed. The distribution that meets the criteria of Coefficient ofDetermination, Chi-Square, and Root Mean Square Error is the Weibull distribution, asevidenced by the probability plots of the Weibull distribution, which closely match the actualdata from various regions. Areas with potential for wind energy to be converted intoelectricity are evaluated based on the percentage of wind speeds exceeding 2 m/s. The areaswith the highest potential are Tuban with a percentage of 56.89%, Malang with 56.71%, andBandung with 50.20%.